Swing-torsion composite friction behavior of CoCrMo/UHMWPE contact interface of artificial knee joint prosthesis implantation materials. (13th February 2019) - Wu, Mingjin; Chen, Kai; Xu, Linmin; Qi, Jianwei; Luo, Yong; Zhang, Dekun
Abstract: Artificial knee replacement has been widely used in clinical medicine, but the motion of the artificial knee prosthesis is very complicated in the human body. The prosthesis suffers wear which further lead to osteolysis and aseptic loosening. Therefore, the artificial knee joint prosthesis material CoCrMo and UHMWPE were studied in this paper, and the swing-torsion composite friction behavior between CoCrMo/UHMWPE contact interfaces is carried out on the artificial knee joint simulator. The tribological behavior and damage mechanism of the CoCrMo/UHMWPE contact interface were studied during the swing-torsion composite motion friction experiment. The changed trend of swing and torsion component friction coefficients in the swing-torsion composite motion are the same as that in the single swing and torsion. UHMWPE is worn more seriously in the swing-torsion composite motion. The main damage mechanism of CoCrMo in the swing-torsion composite motion is abrasive wear and the main damage mechanisms of UHMWPE is abrasive wear and fatigue wear.